ANALISIS HUBUNGAN K3 DENGAN PRODUKTIVITAS KERJA KARYAWAN : Literatur Review - Nur Linda (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Occupational safety and health (K3), including one of the existing maintenance programs in the company. In this study, the design used is Literature Review. The method of searching for article data sources was carried out through the Google Scholar database in the 2019-2023 period to retrieve relevant articles published in Indonesian. Occupational safety and health can have a major effect on employee work productivity. Productive employees have the ability to work, both from the expertise and skills they have.